Effects of semi-domesticated reindeer’s maternal condition on calf survival - Stingo, Diego (SLU/Dept. of Animal Nutrition and Management (until 231231), 2018)
Semi-domesticated reindeer (Rangifer tarandus) husbandry in Sweden depends largely on sustainable management and productivity of the herd. Herd productivity is determined by the survival of the herd’s offspring from each year, which is affected by factors such as weather conditions, forage abundancy and predation. Predation of the reindeer calves by brown bears (Ursus arctos) can become a significant limiting factor of the herd’s productivity. Previous studies suggest the reindeer maternal condition to have an effect on calf survival. Data from pregnant reindeer was collected through the years 2010 to 2016 in two Swedish reindeer herding communities with high predation rates (Gällivare and Udtja) as part of a project investigating reindeer calf mortality due to brown bear predation. Among other factors recorded, females were weighed prior to calving and the presence of their calves on the summer and autumn gatherings was recorded individually. Data on reindeer weight at precalving was analysed in relation to calf survival. Ordinal regression was used to describe the effect of weight by year and herding community over the probability of calf mortality. Results showed a positive effect of female reindeer’s weight at late pregnancy on the odds of survival of the calf until the autumn. The magnitude of the effect of weight was lower than the fixed effect of herding community. Differences in brown bear presence and year-to-year variations can be highly influential on calf survival. The year 2011 was predicted to have the lowest odds of survival, while the reindeer calves in Gällivare community had an overall higher survival rate than the reindeer calves in Udtja.